2017
DOI: 10.1016/j.specom.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The beauty in a beast: Minimising the effects of diverse recording quality on vowel formant measurements in sociophonetic real-time studies

Abstract: Sociophonetic real-time studies of vowel variation and change rely on acoustic analyses of sound recordings made at different times, often using different equipment and data collection procedures. The circumstances of a recording are known to affect formant tracking and may therefore compromise the validity of conclusions about sound changes made on the basis of real-time data. In this paper, a traditional F1/F2-analysis using linear predictive coding (LPC) was applied to the vowels /i u a/ extracted from spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…If the measure of interest is systematically affected by a certain type of device, adjustments could be calculated on participant data to improve comparability across speakers. If speakers make multiple recordings in different sessions, ask them to use the same device each time, and instruct them on device placement and minimizing background noise to increase both audio quality and comparability across sessions. Environmental noise was not a factor in the current study, but it varies considerably in natural settings and could be problematic for many types of acoustic measurements (e.g., De Decker, 2016; Rathke et al., 2017). Consider other creative solutions like mailing participants equipment, instructing them on how to disable speech‐processing apps on their device before recording, asking them to record on two devices simultaneously, or sending them a small device like an inexpensive keychain loaded with a short audio clip containing multiple variations of the measurements of interest and asking them to play it aloud before recording.…”
Section: Discussionmentioning
confidence: 91%
“…If the measure of interest is systematically affected by a certain type of device, adjustments could be calculated on participant data to improve comparability across speakers. If speakers make multiple recordings in different sessions, ask them to use the same device each time, and instruct them on device placement and minimizing background noise to increase both audio quality and comparability across sessions. Environmental noise was not a factor in the current study, but it varies considerably in natural settings and could be problematic for many types of acoustic measurements (e.g., De Decker, 2016; Rathke et al., 2017). Consider other creative solutions like mailing participants equipment, instructing them on how to disable speech‐processing apps on their device before recording, asking them to record on two devices simultaneously, or sending them a small device like an inexpensive keychain loaded with a short audio clip containing multiple variations of the measurements of interest and asking them to play it aloud before recording.…”
Section: Discussionmentioning
confidence: 91%
“…Measurements of mean F0 and SCPP (smoothed cepstral peak prominence) proved relatively robust across devices, but jitter and shimmer did not. The findings of Jannetts et al (2019) and Rathcke et al (2017) indicate that ideally, device specifications should be the same for all participants. This poses a problem for projects such as SDATS, as there are currently more than 20 major vendors within the smartphone industry (Metodiev 2019).…”
Section: Challenge 4: Recording Qualitymentioning
confidence: 91%
“…They found that recordings on a first-generation iPhone were suitable for formant analysis, as the overall shape of the vowel space does not seem to be affected substantially. More recently, Rathcke et al (2017) studied the effects of different equipment on F1 and F2 measurements in real-time sociolinguistic analyses, reporting that formant measurements using LPC tracing are sensitive to the technical specifications of the microphones used at different points in time. Their key recommendation is that linguists should keep the recording equipment controlled in order to maximize comparability between recording sessions.…”
Section: Challenge 4: Recording Qualitymentioning
confidence: 99%
“…Some sociophonetic studies have considered the effects of poor quality recordings on acoustic analysis methods (e.g. Rathcke et al 2016), and this research is incredibly valuable to practitioners who need to assess what methods are suitable given the recording characteristics. Sociophonetic data collection is, of course, conducted according to the requirements of the study.…”
Section: Elicitation and Recording Methodsmentioning
confidence: 99%